2009
DOI: 10.1158/1078-0432.ccr-08-2245
|View full text |Cite
|
Sign up to set email alerts
|

miR-200 Expression Regulates Epithelial-to-Mesenchymal Transition in Bladder Cancer Cells and Reverses Resistance to Epidermal Growth Factor Receptor Therapy

Abstract: Purpose The epithelial to mesenchyme transition (EMT) is a cell development-regulated process in which noncoding RNAs act as crucial modulators. Recent studies have implied that EMT may contribute to resistance to epidermal growth factor receptor (EGFR)-directed therapy. The aims of this study were to determine the potential role of microRNAs (miRNAs) in controlling EMT and the role of EMT in inducing the sensitivity of human bladder cancer cells to the inhibitory effects of the anti-EGFR therapy. Experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
282
5
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(305 citation statements)
references
References 42 publications
(53 reference statements)
15
282
5
3
Order By: Relevance
“…A handful of studies has found that various miRNAs are involved in the development of bladder cancer (31). For example, miR-126 and miR-182 are related to urinary bladder cancer (12); miR125b inhibits the development of bladder cancer through E2F3 (32); miR-143 serves as a tumor inhibitor of bladder cancer (13); miR-200 regulates EMT in bladder cancer cells and reverses the resistance to epidermal growth factor (EGF) receptor (33).…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies has found that various miRNAs are involved in the development of bladder cancer (31). For example, miR-126 and miR-182 are related to urinary bladder cancer (12); miR125b inhibits the development of bladder cancer through E2F3 (32); miR-143 serves as a tumor inhibitor of bladder cancer (13); miR-200 regulates EMT in bladder cancer cells and reverses the resistance to epidermal growth factor (EGF) receptor (33).…”
Section: Discussionmentioning
confidence: 99%
“…A strong increase in the phosphorylation of Cdc25C at the Ser-216 site, which prevents Cdc25C dual-specificity phosphatase from dephosphorylating and activating cyclin B1/Cdc2 (Peng et al, 1997) There is increasing evidence that EMT may contribute to the resistance to different therapies in cancer (Thomson et al, 2005;Yauch et al, 2005;Arumugam et al, 2009). The miR-200 family, which regulates EMT, has also been reported in the sensitization of cancer cells to different drugs, for example, to the EGFR-targeting molecule gefitinib in bladder carcinoma (Adam et al, 2009) or to paclitaxel in breast, ovarian and endometrial cancers (Cochrane et al, 2010). A current focus in drug discovery is to develop agents that target the cell cycle checkpoints, aiming at increasing or decreasing the amount of arrested cells at these points (reviewed in DiPaola, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Their silencing confers resistance to EGFR in mesenchymal bladder cancer cells that can be reversed by the expression of miR-200 163 .…”
Section: Emt and Metastasismentioning
confidence: 99%